1985
DOI: 10.1159/000465735
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of Guanosine in Human Erythrocytes

Abstract: The metabolism of guanosine in human erythrocytes has been studied in two different experimental systems - direct incubation and dialysis incubation - the latter allowing continuous addition and removal of substances. Intra- and extracellular purine compounds were analyzed using high-performance liquid chromatography (HPLC). At 37 °C, a normal pH (7.4) and a favorably high concentration of inorganic phosphate, guanine nucleotides were synthesized at a substance rate of about 0.17 mmol • h^-1 (calculated per li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1998
1998
1998
1998

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…A problem is that even with storage media which give a comparatively high initial, intracellular pH, the resulting higher glycolysis rate causes an increased formation of acid metabolites so that the situation during the 5-6th week will not be very much different. In the PAGGS-S/M AS the formation of guanine nucleotides seems to give some improvement due to the fact that GTP can substitute for ATP in some functions [59]. In Erythro-Sol the elevating effect on the intracellular pH together with the availability of adenine and phosphate promotes the maintenance of both ATP and 2,3-DPG; a stock of adenylates is built up at the early phases of storage.…”
Section: Evaluation Of Storage Proceduresmentioning
confidence: 99%
“…A problem is that even with storage media which give a comparatively high initial, intracellular pH, the resulting higher glycolysis rate causes an increased formation of acid metabolites so that the situation during the 5-6th week will not be very much different. In the PAGGS-S/M AS the formation of guanine nucleotides seems to give some improvement due to the fact that GTP can substitute for ATP in some functions [59]. In Erythro-Sol the elevating effect on the intracellular pH together with the availability of adenine and phosphate promotes the maintenance of both ATP and 2,3-DPG; a stock of adenylates is built up at the early phases of storage.…”
Section: Evaluation Of Storage Proceduresmentioning
confidence: 99%
“…CTP inhibited G6PD competitively with glucose-6-phosphate (K; = 1.7 mmol/1 CTP) and non-competitively with NADP (K; mmol/1 CTP) [5]. Since the intraerythrocytic concentration of CTP ranges from 0.77 to 1.74 mmol/1 [2,3] in P5Nase deficiency and since the intraerythrocytic concentration of NADP (~ 1 pmol/l) is below its Km of ap-7.8 activity, as well. Thus, the physiologic signif icance, if any, of an increased intraerythrocytic concentration of CDP-choline remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Torrance and Whittaker [9] originally de scribed an unidentified cytidine compound(s) of approximately 1 mmol/1 concentration in the RBC in P5Nase deficiency. Subsequent studies by Ericson et al [3] and Swanson et al [2] have identified increased concentra tions of CDP-choline (0.93-1.51 mmol/1) in the P5Nase-deficient erythrocyte. Paglia et al [1] found a CDP-choline concentration of 0.31-0.45 mmol/1 in their case of unex plained hemolytic anemia.…”
Section: Embden-meyerhof Pathwaymentioning
confidence: 99%
See 1 more Smart Citation